Current status and response to the global obesity pandemic : proceedings of a workshop - Callahan, Emily A. (the National Academies Press, 2019)
"The increasing prevalence and burden of obesity transcends borders, straining populations worldwide. Data shows that 50 million girls, 74 million boys, 390 million women, and 281 million men were estimated to have obesity in 2016 (NCD-RisC, 2017). The National Academies of Sciences, Engineering, and Medicine convened a workshop on October 9, 2018 to address the status of the global obesity pandemic and discuss diverse approaches to manage this problem. Speakers examined the collective prevalence, costs, and drivers of obesity around the world using cross-cultural comparisons. Panels and group discussions emphasized the need to reduce disparities in prevention and treatment efforts and to generate new policy and system initiatives related to nutrition and physical activity worldwide. This publication summarizes the presentations and discussions from the workshop"--Publisher's description